A "Molecular Water Pipe": A Giant Tubular Cluster Dy72 Exhibits Fast Proton Transport and Slow Magnetic Relaxation. Issue 48 (7th November 2016) - Qin, Lei; Yu, You‐Zhu; Liao, Pei‐Qin; Xue, Wei; Zheng, Zhiping; Chen, Xiao‐Ming; Zheng, Yan‐Zhen
Abstract : A lanthanide cluster, PCC‐72, which is the second largest, with 72 Dy(III) ions assembled into an unprecedented tubular structure, is synthesized. Remarkably, PCC‐72 exhibits superionic proton conductivity (>10 −4 S cm −1 ) under both ambient (with relative humidity RH < 75%) and hot ( T > 90 °C, RH = 95%) conditions. Moreover, slow magnetic relaxation is observed, making PCC‐72 the largest Dy(III) cluster that is a single‐molecule magnet.